Working Together: How South Australian Libraries Shared Their COVID-19 Experiences through a Student-led Project. Issue 3 (3rd July 2021) - Walkley Hall, Liz; Best, Ainsley; Dwivedi, Akrati
ABSTRACT: 2020 was a challenging year in so many ways. Undertaking student placements as part of a professional accreditation course for LIS (Library and Information Studies) was one challenge that students, course coordinators, and industry had to face together. Working together, two University of South Australia students partnered with a local industry professional in a personal professional capacity to complete their placement. The project they undertook was to design and deliver a symposium for library and information professionals. This article uses the lens of Tuckman's Small Group Development model to demonstrate how this project was delivered.